Relationship Between ABO blood Group and Carcinoma of Cervix in South Gujarat Women - Tailor, Hemali J; Rajani, Anisha Dipakbhai; Hathila, Rasik N; Patel, Prashant R (Annals of Pathology and Laboratory Medicine, 2020)
Introduction: Cervical cancer is one of the leading causes of death from cancer and second most common cancer, next only to breast cancer among women worldwide and is the most common female cancer in developing countries as well. In India, cervical cancer is the most common women related cancer, followed by breast cancer. Several studies have suggested an association between blood type A and cervical dysplasia/cancer. The aim of this study was to document the relationship between cervical cancer and ABO blood group in South Gujarat population. Materials and Method: The present study was an observational descriptive study and was conducted retrospectively among 147 cases of cervical cancer patient admitted in tertiary care hospital, Surat and diagnosed by histopathologically over period of two and half years. Patients personal details were retrieved from Department of pathology and ABO blood group were retrieved from Department of Immunohaematology and blood transfusion. All details were entered in Microsoft excel and analyzed by descriptive statistics. Results: Among 147 cases, maximum cases were found in age group f 30-44 years and showed preponderance of blood group A(31.97%) followed by group B (29.93%), O (27.21%), AB (10.88%). Conclusion: The frequency of types A, B, AB and O in cervical cancer was different to the general healthy population in South Gujarat region.